2021
DOI: 10.1159/000517266
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of Glutathione S-Transferase M1 Is Associated with Patients with Ovarian Endometriosis and Endometriosis-Related Primary Infertility

Abstract: <b><i>Background:</i></b> The aim of the study was to investigate the role of the genetic variation of glutathione S-transferase M1 (<i>GSTM1</i>) in the development of ovarian endometriosis and endometriosis-related primary infertility risk. <b><i>Methods:</i></b> This case-control study included 564 women with ovarian endometriosis and 576 normal women in the control group in northern China. The polymorphism of GSTM1 was genotyped by polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Oxidative stress involvement in unexplained infertility and endometriosis has been previously supported [29]. Zhang et al demonstrated that the GSTM1-null genotype is an independent risk factor for the development of endometriosis, and it is involved in primary infertility [13]. Mavrogianni et al revealed that the absence of GSTM1 gene detected in women with endometriosis, may indicate a possible involvement of the detoxifying metabolic pathway in the pathophysiology of the disease.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Oxidative stress involvement in unexplained infertility and endometriosis has been previously supported [29]. Zhang et al demonstrated that the GSTM1-null genotype is an independent risk factor for the development of endometriosis, and it is involved in primary infertility [13]. Mavrogianni et al revealed that the absence of GSTM1 gene detected in women with endometriosis, may indicate a possible involvement of the detoxifying metabolic pathway in the pathophysiology of the disease.…”
Section: Discussionmentioning
confidence: 89%
“…Like the other members of the glutathione-S-transferases family, GSTM1 act also as a hormone binding protein. The corresponding encoding sequence is well recognized for its high polymorphism [13][14][15]. Due to an extended deletion of the gene (approximately 10 kb), a null activity allele is produced, leading to a non-functional protein [4,12,16].…”
Section: Introductionmentioning
confidence: 99%